Lessons in creativity from musical theatre characters - Kaufman, James C.; Rowe, Dana P. (Routledge, 2024)
"Lessons in Creativity from Musical Theatre Characters marries art and science with a new and exciting collaboration between one of the world's leading creativity scholars and an internationally renowned musical theatre composer. This book is a blend of cutting-edge research, juicy anecdotes, lived experience, hands-on activities, and gentle advice that takes readers on a journey to explore and enhance their own creativity. Each chapter addresses a key aspect of creativity, from how to overcome blocks to understanding one's personal strengths. The authors shatter creativity myths (such as the tormented artist or having one big break) that may be harming the reader's potential growth. Probing questions, fun quizzes, and engaging exercises will help the reader reflect on the material and develop strategies for their next step. All throughout, the readers can learn from the tales of Sweeney Todd, Maria Von Trapp, Alexander Hamilton, Christine Daa,̌ and countless others to inspire their own creativity. This book is ideal for theatre or creativity scholars, students and aspiring professionals in the performing arts, and devoted fans alike"--